The Rate of Unequal Crossing Over in the dumpy Gene from Drosophila melanogaster. - Carmon, A.; Larson, M.; Wayne, M.; Macintyre, R. (Journal of Molecular Evolution, 2010)
The PIGSFEAST (PF) exon of the Drosophila dumpy gene is undergoing concerted evolution by the process of unequal crossing over. We have developed a long-range PCR-based assay to amplify the approximately 12 kb long exon which contains variable numbers of 303 or 306 nt long repeats in a tandem array. We applied this procedure to mutation accumulation lines of Drosophila melanogaster established by M. Wayne and L. Higgins. Nine new repeat length variants were found in these lines allowing us to measure the rate of unequal crossing over in the PF exon. The rate, which for several reasons is an underestimate, is 7.05 x 10(-4) exchanges per generation.